Features of Automation of the Lesson Schedule Through the Programming Language in Higher Military Educational Institutions. - T.Sh.Jumaniyozov; F.Sh.Davronov (Universitas Muhammadiyah Sidoarjo, 2022)
Information technology has become not only an integral part of people's daily lives, but also the activities of government and business institutions. In addition, the active and rational use of information technology allows the organization to maintain a high level of competitiveness, regardless of the size, scope and scope of activities. Thus, in the context of rapid and continuous development of information technologies for such organizations, it is necessary to improve the existing material resources and software used individually and as a whole information architecture. In the process of compiling the table, scientific research begins in the middle of the last century. Scheduling is available not only in the field of education, but also in the field of transport, industry, public services and more.